Effects of Transcutaneous Electrical Nerve Stimulation on Proinflammatory Cytokines: Systematic Review and Meta-Analysis - Tábata Cristina do Carmo Almeida; Francisco Winter dos Santos Figueiredo; Valter Cordeiro Barbosa Filho; Luiz Carlos de Abreu; Fernando Luiz Affonso Fonseca; Fernando Adami (Mediators of Inflammation)
The mechanism of pain reduction involves bidirectional processes of pain blocking (nociception) and reductions in the levels of proinflammatory cytokines in the blood. Does transcutaneous electrical nerve stimulation (TENS) reduce blood levels of proinflammatory cytokines? For this systematic review, we searched in six databases to identify randomized controlled trials with the criteria: humans older than 18 years (adults), use of TENS in the experimental group, and having at least one pre- and postintervention blood level of at least one proinflammatory cytokine. The risk of bias and the level of evidence were assessed. Five studies were included involving 240 participants. The heterogeneity of the studies was high (I2: 85%); therefore, we used a random-effects meta-analysis. It was observed through the meta-analysis synthesis measures that there were statistically significant differences following the use of TENS to reduce the general group of cytokines. When grouped by chronic disease, by postoperative settings, or by individual studies in the case of IL-6, it was observed that the significant reduction of cytokines related to the use of TENS was maintained. The use of TENS reduced the blood levels of proinflammatory cytokines (we observed a protective factor of TENS in relation to inflammation). The protocol of the systematic review was registered in PROSPERO, CRD42017060379.